Rancang Bangun Aplikasi Informasi Candi berbasis Teknologi Augmented Reality pada Smartphone Android (Studi Kasus: Candi Ngetos, Nganjuk) - Diandra Amiruddin Firmansyah; Herman Tolle; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Temple is one of sacred buildings that used for worship by Hindus and Buddhists in Indonesia. Ngetos Temple is one kind temple which still exist and has suffered serious damage. Need technical handling for Ngetos Temple restoration. However, the refurbishment process also requires archeological technical studies that require considerable time and cost, there is another way restoration to reduce the time constraints of the restoration process by using Augmented Reality (AR) technology. AR is a technology that used in real-world modeling into computer systems to help and support human activities. AR can be implemented with Oriented FAST and Rotated BRIEF (ORB) algorithm. This algorithm is open source. To implement this algorithm, a supporting library is required for implement all functions of the ORB algorithm, in this study using the OpenCV library. For that researchers build temple information application based on AR technology on android smartphone that implement ORB algorithm. The application scans the pattern on the image that has been taken by the camera then displays the 3D object of the temple based on the pattern. The results of 3D objects in the form of a whole temple that can represent the temple that has been restored.